Meningkatkan Keterampilan Berbicara Melalui Permainan Tradisioanal “Cublak-Cublak Suweng” di Madrasah Ilmu Al-qur’an Tembelang Jombang - Ratnaningtyas, Oktavia (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2024)
This research aims to describe the application of speaking skills through the traditional game cublak cublak suweng as well as the advantages and disadvantages of this game in improving Arabic speaking skills. In this research, the researcher used descriptive qualitative research by explaining the stages of implementing the cublak cublak suweng game in Arabic speaking skills and the steps of the game. With this cublak cublak suweng game which makes female students more enthusiastic and active in learning, the female students' speaking skills tend to improve because they are more confident in expressing their opinions using Arabic with more fluent makhorijul letters than before and correct intonation. Meanwhile, the advantage of implementing this game is that female students are more enthusiastic, focused and active while learning speaking skills. On the other hand, the disadvantage of implementing the cublak cublak suweng game is that the sound of female students' laughter and cheering can disrupt the implementation of learning in other classes, and this game is still not considered a language learning program, but only as a distraction.